2001
DOI: 10.1200/jco.2001.19.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Paclitaxel, Ifosfamide, and Cisplatin as Second-Line Treatment in Relapsed Small-Cell Lung Cancer

Abstract: In the present phase II study, the PIC combination seemed highly active and tolerable in patients with relapsed SCLC when it was administered as second-line treatment. Given the present experience, an evaluation of the PIC regimen as front-line treatment of SCLC is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 24 publications
2
31
1
Order By: Relevance
“…Toxicity in the CIP arm was greater than reported elsewhere; however, the phase I dose-escalating study (Papadimitriou et al, 2001) used prophylactic G-CSF and had febrile neutropaenia in one patient out of eight treated at doses comparable with ours, and the phase II trial (Kosmas et al, 2001) reported less frequent highgrade haematological toxicity but used only 1.5 g m À2 ifosfamide, which is 70% lower than the dose we used. Overall, the results of this study indicate low feasibility of the CIP regimen with a starting dose of 5 g m À2 ifosfamide, at least without prophylactic G-CSF.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Toxicity in the CIP arm was greater than reported elsewhere; however, the phase I dose-escalating study (Papadimitriou et al, 2001) used prophylactic G-CSF and had febrile neutropaenia in one patient out of eight treated at doses comparable with ours, and the phase II trial (Kosmas et al, 2001) reported less frequent highgrade haematological toxicity but used only 1.5 g m À2 ifosfamide, which is 70% lower than the dose we used. Overall, the results of this study indicate low feasibility of the CIP regimen with a starting dose of 5 g m À2 ifosfamide, at least without prophylactic G-CSF.…”
Section: Discussioncontrasting
confidence: 47%
“…Shortly after the start of this clinical trial, in a phase I and a phase II trial of cisplatin and paclitaxel combined with ifosfamide, significant activity against ovarian epithelial cancer was noted. The regimen was feasible with ifosfamide doses up to 5 g m À2 (Kosmas et al, 2001;Papadimitriou et al, 2001).…”
mentioning
confidence: 99%
“…One trial where patients were treated with a combination of paclitaxel, cisplatin, and ifosfamide showed a response rate of 70%. Although the median survival of the platinum-resistant patients was not reported separately, the median survival of all patients treated (20 with platinum resistant and 13 with platinum sensitive disease) was 7 months (40).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these preclinical in vitro experimental data, we believe that the sequence and infusion times regarding docetaxel and ifosfamide, as applied in the present study, might lead to potential in vivo synergism between these two drugs (Kearns et al, 1995). Moreover, our prior experience with paclitaxel -ifosfamidecisplatin (Kosmas et al, 2000a, b;2001) or docetaxel -ifosfamide -cisplatin (Kosmas et al, 2002) combinations has demonstrated their feasibility in phase I and phase II studies in advanced solid tumours and lung cancer in particular.…”
Section: Discussionmentioning
confidence: 75%